2014
DOI: 10.1002/bem.21883
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of weak magnetic fields on radical pairs

Abstract: It is proposed that radical concentrations can be modified by combinations of weak, steady and alternating magnetic fields that modify the population distribution of the nuclear and electronic spin state, the energy levels and the alignment of the magnetic moments of the components of the radical pairs. In low external magnetic fields, the electronic and nuclear angular momentum vectors are coupled by internal forces that outweigh the external fields' interactions and are characterized in the Hamiltonian by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 45 publications
(61 reference statements)
3
78
0
1
Order By: Relevance
“…In its present form, the RPM predicts similar effects for a static field and a low-frequency (such as 50 Hz) time-varying MF, so effects of the 10-mT field in the presence of the stronger geomagnetic field are not easily explained by the RPM. The findings of this study therefore emphasize the need to develop theoretical understanding of possible specific effects of weak low-frequency alternating MFs, as discussed by Vanderstraeten & Gillis [9] and Barnes & Greenebaum [11].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In its present form, the RPM predicts similar effects for a static field and a low-frequency (such as 50 Hz) time-varying MF, so effects of the 10-mT field in the presence of the stronger geomagnetic field are not easily explained by the RPM. The findings of this study therefore emphasize the need to develop theoretical understanding of possible specific effects of weak low-frequency alternating MFs, as discussed by Vanderstraeten & Gillis [9] and Barnes & Greenebaum [11].…”
Section: Discussionsupporting
confidence: 52%
“…at MF levels that are considerably lower than the reference levels of the International Commission on Non-Ionizing Radiation Protection [6], for exposure of the general public (200 mT) and occupational exposure (1000 mT). There are currently no generally accepted mechanisms that could explain biological effects of weak ELF MFs at the levels suggested by epidemiological studies, although hypothetical mechanisms have been suggested, and there is wide interest in magneto-sensitive radical pair reactions as the basis for biological effects of weak MFs [7][8][9][10][11]. Because of the very low interaction energy, direct DNA damage by ELF MFs is not plausible, but there is evidence that ELF MFs might enhance the effects of DNA damaging agents [12].…”
Section: Introductionmentioning
confidence: 99%
“…Also biological responses of cultured HUVEC cells, including changes in cellular superoxide levels, were influenced by the relative orientations of a 50  μ T static MF and oscillating MFs at the Zeeman resonance of 1.4 MHz [14]. Resonances at the ELF range have been proposed to affect radical pair reactions [15], but further theoretical work is required to understand the in vitro findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a great number of data on the significant effects of NT MW on the enzymatic activity in brain tissues and immune properties of organism [6], [7], the nature of primary metabolic target(s), through which NT MW effects are realized, is not clear yet. Since the phenomenon of the biological effect of NT MW cannot be explained from the point of classic thermodynamics [8], it is clear that the electron, which has high charge to mass ratio could serve as a target for such an extremely low energy impact [9], [10]. Since the water content of head skin and sub-skin tissues has high sorption properties for NT MW, the energy of the latter cannot reach to brain tissue.…”
Section: Introductionmentioning
confidence: 99%